Investigation of anti-depressant effect of aqueous and ethanolic extract of Cydonia oblonga in rats. (June 2020) - Din Ganaie, Mehraj U.; Behl, Tapan; Nijhawan, Priya; Sachdeva, Monika; Khan, Nadeem
Abstract: Background: Depression is a mood disorder characterized by feeling of sadness, change in sleep and appetite and loss of interest. Purpose: The current study enumerates the intrinsic role of Cydonia oblonga Mill fruit extract in methyl isobutyl ketone induced depression in Rats. Methods: Depression was prompted through injection of methyl isobutyl ketone (MIBK) (100 mg/kg i.p) twice daily for one month. 54 rodents were used in the study. Total 9 groups was included in the present study. After treatment, for 15 days all groups were evaluated for behavioral testing namely Forced Swim Test (FST) and Tail Suspension Test (TST). Results: The results presented that of Cydonia oblonga Mill fruit exhibit antidepressant effect. Consequently, a gradual decrease was observed in immobility time (P < 0.05) in contrast to normal group and depressed group. On treatment with aqueous extract of Cydonia oblonga (AECO) and ethanolic extract of Cydonia oblonga (EECO) 200 mg/kg and imipramine 15 mg/kg immobility period gradually fall. Co-administration of imipramine and of Cydonia oblonga Mill extract indicate alteration in biochemical parameters. Conclusion: It was observed in the study that co-administration of aqueous extract of Cydonia oblonga (AECO) and ethanolic extract of Cydonia oblonga (EECO) with small dose of imipramine appears to have therapeutic effect in the treatment of depression. Highlights: Depression is the life threatening disorder as it is the major cause of morbidity and mortality. At present depression is the main cause of suicide in both men and women. The menace of depression is increasing at an alarming rate as it move from 5% to 12% in men and 10%–25%.